PENGARUH LATIHAN COMBINATION ZIG-ZAG DRILL TERHADAP KELINCAHAN PADA PEMAIN SSB YAPORA PRATAMA U-12 PEKANBARU - Rafni Wirma Hartati; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research was the less agility of SSB Yapora Pratama U-12 Pekanbaru player is still lacking, it is seen from the various trials and official matches that he played, and this is one of the causes of the defeat. The design of this research was experiment design, the population of this research were SSB Yapora Pratama U-12 Pekanbaru player, the sampel of this research were 14 palayer, all of the population. The technique of taking data was from pre-test and post-test. The instrument that used in this research was dogging run test, that purposed to measure the agility. As a free variable was combination zig-zag drill (x), mean while the bourd variable was the agility (y). after that, the data processed statistically, to try out the normality used liliefors test in significant taraf 0,05 α. The hypotheses that proposed found there is effect of combination zig-zag drill practice forward the agility. Based on t-test analysis found tcount amount 6,18 and ttable 1,771, it’s mean that tcount >ttable. It can be concluded, Ha was accepted. The conclusion, there was a significant effect from combination zig-zag drill practice forward the agility of SSB Yapora Pratama U-12 Pekanbaru player.Keyword: Combination zig-zag drill, agility,Football